Medicated Lollipops: A New Drug Delivery System for Pediatric Patients - Shashank R (Jordan Journal of Pharmaceutical Sciences, 2025)
A medicated lollipop is a kind of sugary treat that is typically made of hard candy and placed on a stick so that it may be licked or sucked on. There are many flavors and styles of lollipops available. Alternative names include sticky-pop, Lolly and sucker. There are various dosage forms available on the market; nevertheless, an additional dosage form that functions both locally and systematically may be required. The benefits of current research include longer dosage form retention in the oral hollow space, higher bioavailability, and a decrease in gastric inflammation through first metabolism. Lollipops are medicinal dose forms with flavors that are meant to be sucked and kept in the mouth or throat. The sweetened foundation of the lollipops typically contains one or more medications. The customary dosage for medications, tablets, and syrups.